Editorial [Hot Topic: Depression (Part 2) (Guest Editors: Ronald S. Duman and John H. Kehne)] - Duman, Ronald S.; Kehne, John H. (CNS & Neurological Disorders - Drug Targets, 2007)
Depressive illness is a devastating disorder that affects 18.8 million American adults (9.5% of the adult population) and is the leading cause of disability in the U.S. and other developed countries. Depression occurs twice as frequently in women relative to men. When untreated, depressive episodes increase in severity and frequency, and can lead to suicide. The symptoms of major depressive disorder include sad or irritable mood, feelings of guilt, worthlessness, hopelessness, and lack of interest or pleasure, as well as cognitive dysfunction and persistent sleep, appetite, and physical abnormalities. Genetic, biological, and psychological factors can contribute to the development of depressive illness, though the relative contributions of these factors vary considerably from individual to individual. Stress can play an important role in causing and/or precipitating depressive episodes, and the ways in which stress interacts with underlying biological vulnerabilities to precipitate depression is an important area of current research. Such a complex, syndromal illness with genetic and environmental determinants poses many problems for the development of effective therapeutic interventions. Currently used antidepressant drugs have been identified largely by serendipity. First generation antidepressant drugs increase synaptic availability of monoamines by either blocking serotonin and/or norepinephrine reuptake sites or by inhibiting monoamine oxidase, and while clinically effective, the usefulness of these drugs is limited by their side effects. Second generation antidepressants include the selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors. Side effects for these drugs are reduced, but still problematic (e.g., sexual dysfunction, agitation/ jitteriness, headache, nausea, nervousness and insomnia). All antidepressants generally require a minimum of 3-4 weeks of administration before they become clinically effective. The explanation for why chronic treatment is needed has been the topic of extensive research and has stimulated the search for more rapidly acting antidepressants. Additionally, only about 65 percent of patients respond to currently available drugs, leaving a significant non-responsive subpopulation without effective treatment. This limited efficacy, as well as time dependence and side effect profile of current antidepressants underline a clear need for new and improved antidepressant drugs. There have been significant efforts to identify novel targets for the development of more effective and faster acting antidepressant medications. One potential major breakthrough is ketamine, a glutamate-NMDA antagonist, which is a subject of one of the reviews in part 1 (April 2007) of this “Depression Hot Topics Issue”. Recent studies demonstrate that a single low dose of ketamine can produce a rapid antidepressant response that lasts for several days. The mechanisms underlying this effect are discussed, as well as ways to develop more selective agents while limiting the abuse potential and side effect profile of ketamine. This issue also highlights related areas of drug development that are directed at glutamatergic and GABAergic neurotransmitter receptor systems. These comprise the subjects of two other reviews that describe efforts to modulate the major excitatory and inhibitory neurotransmitter systems for antidepressant pharmacotherapy. The modulation of monoamine systems remains a focus of drug efforts, including the development of triple reuptake inhibitors. In addition, the galanin neuropeptide system is being targeted, and may act at least in part via modulation of serotonin neurotransmission. Another area of intense research and drug development interest that is highlighted in part 2 of this issue is stress and CRF receptors remain a major drug target for the treatment of depression as well as anxiety. Studies of stress have also contributed to a neurotrophic hypothesis of depression, with basic and clinical studies demonstrating that repeated stress exposure causes atrophy and loss of neurons and glia in limbic brain structures, which can be reversed by antidepressant treatment.